Hormonal, metabolic and perceptual responses to different resistance training systems - Charro, M. A.; Aoki, M. S.; Coutts, A. J.; Araujo, R. C.; Bacurau, R. F. (The Journal of Sports Medicine and Physical Fitness, 2010)
AIM: The purpose of the present study was to compare the effect of different resistance training systems (Multiple-set [MS] and Pyramid [P]) on hormonal, metabolic and perceptual markers of internal load. METHODS: Ten healthy men performed two resistance training sessions (MS and P) which consisted of three exercises (bench press, peck deck and decline bench press) with the same total volume of load lifted. The training sessions were performed 14 days apart and allocated in a counter-balanced order. Hormonal (plasma insulin, growth hormone [GH], testosterone and cortisol) and metabolic (blood glucose and lactate) responses were assessed before and after each exercise bout. Session rating of perceived exertion (session RPE) was taken 30-min following each bout. RESULTS: No difference was observed for session-RPE between P and MS bouts (P>0.05). Plasma GH, cortisol and lactate increased significantly after exercise both bouts (P<0.01), but there were no significant changes between MS and P (P>0.05). CONCLUSION: It is concluded that the acute bout of resistance exercise following MS and P systems provide similar training strain when the total volume of load lifted is matched.